Penerapan Prinsip-Prinsip Cognitive Behavior Therapy (BT) untuk Meningkatkan Self-Esteem Pada Remaja Perempuan - Amalia, Nafisa Alif (Persona:Jurnal Psikologi Indonesia, 2018)
Self-esteem accorded a prominent role in the transition adolescence to adulthood. High self-esteem was associated with life satisfaction and predicts success and well-being in life domains. Otherwise, low self-esteem predicted depressive symptoms and as an indicator of various forms of internalizing and externalizing psychopathology. This study aimed to determine effectiveness the principles of Cognitive Behavior Therapy (CBT) to increase self-esteem. This study uses single-subject research design. The participant of this study is a 13 years 8 months old girl who has low self-esteem. Self-esteem was measured by a Coopersmith Self-Esteem Inventory (CSEI) from Coopersmith (1967), adolescent’s behavior was measured by Child Behavioral Checklist (CBCL), and supported by interview with adolescent and parent. This intervention consists of three stages, such as the pre-intervention that consists of one session, the intervention that consists of eight sessions, and the post-intervention that consist of one session. The result of this study indicates that CBT can increase self-esteem, especially in certain domains, such as school and general self. Meanwhile, adolescent’s behavior also changes, especially in thought problem aspect. However, other problem experienced by adolescent can be obstacle to effectiveness the principles of Cognitive Behavior Therapy (CBT) to increase self-esteem.